![](https://iknow-base.cdn.bcebos.com/lxb/notice.png)
计算:(1)-40-(-19)+(-24);(2)(-5)×(-8)-(-28)÷4;(3)(12+56?712)÷(?136);(4)-22
计算:(1)-40-(-19)+(-24);(2)(-5)×(-8)-(-28)÷4;(3)(12+56?712)÷(?136);(4)-22-(-2)2-23×(-1)...
计算:(1)-40-(-19)+(-24);(2)(-5)×(-8)-(-28)÷4;(3)(12+56?712)÷(?136);(4)-22-(-2)2-23×(-1)2013.
展开
1个回答
展开全部
(1)原式=-40+19-24=-45;
(2)原式=40+7=47;
(3)原式=(
+
-
)×(-36)=-18-30+21=-27;
(4)原式=-4-4+8=0.
(2)原式=40+7=47;
(3)原式=(
1 |
2 |
5 |
6 |
7 |
12 |
(4)原式=-4-4+8=0.
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询